2009
DOI: 10.1111/j.1468-3083.2008.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus ointment 0.1% in the treatment of allergic contact eyelid dermatitis

Abstract: Topical tacrolimus is a promising alternative in patients with allergic contact eyelid dermatitis. Therapy was effective by 1 month and was well tolerated. These preliminary results merit a larger, controlled, study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…[18][19][20] Several studies have shown that topical tacrolimus significantly improved the skin thickening and lichenification as reflected by reduced dermal thickness in chronic AD lesions. [21][22][23] These results suggested that in addition to immune suppressive effect, tacrolimus may also modulate the physiological functions of dermal fibroblasts. Tacrolimus is best known to exhibit its pharmacological effects on inflammatory cell including T cells, macrophages, eosinophils and neutrophils.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…[18][19][20] Several studies have shown that topical tacrolimus significantly improved the skin thickening and lichenification as reflected by reduced dermal thickness in chronic AD lesions. [21][22][23] These results suggested that in addition to immune suppressive effect, tacrolimus may also modulate the physiological functions of dermal fibroblasts. Tacrolimus is best known to exhibit its pharmacological effects on inflammatory cell including T cells, macrophages, eosinophils and neutrophils.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to treating AD, tacrolimus has also been reported to be effective for treating certain fibrotic skin disorders such as scleroderma . Several studies have shown that topical tacrolimus significantly improved the skin thickening and lichenification as reflected by reduced dermal thickness in chronic AD lesions . These results suggested that in addition to immune suppressive effect, tacrolimus may also modulate the physiological functions of dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently many reports suggest the wide use of cosmetic as well as their harmful effects in terms of various skin allergies. [7,8] Many studies have been conducted out that report the allergic response to the cosmetic products in different age and gender groups throughout the world, however, in our knowledge, there is no survey-based study conducted out in India that suggests the effects of cosmetic products on people. The present study is thus planned to collect the data on allergic responses of the different beauty products in different age, gender, and the people belonging to different economic classes.…”
Section: Introductionmentioning
confidence: 94%
“…Therapy was effective by four weeks and was well tolerated. Previous studies have indicated the efficacy of tacrolimus 0.1% ointment in nickel‐induced ACD, allergic contact eyelid dermatitis and allergic contact hand eczema . By contrast with these earlier studies, the present study included various types of allergen and locations of ACD.…”
Section: Numbers and Percentages Of Patients (N = 82) With Allergic Cmentioning
confidence: 99%